Knowledge management practices in academic institution: A proposed concept - Zainuddin, Ahmad; Haron, Haryani; Noordin, Siti Arpah; Hashim, Dang Merduwati; Sahid, Noor Zaidi; Johari, Mad Khir (2004)
The information age, facilitated by the development of information communication technology, leads to an emergence of a new type of economy called knowledge economy.As the world becomes borderless, Malaysia will have to face insurmountable global competitiveness.The challenge of competitiveness and productivity that Malaysia has to face is substantially higher. Therefore a quantum leap in total factor productivity is needed and every factor of production must be made to work smarter. Thus, to be able to work smarter for sustainability, Malaysia has to move to knowledge economy as soon as possible.Academic institutions, which are involves in knowledge-intensive activities must also be prepared to face knowledge economy.Therefore, they must realize that knowledge is the core resources for them to stay competitive.This paper describes a conceptual framework in adopting knowledge management practices or initiatives in institute of higher learning.It was developed as part of the Knowledge Management initiatives at the University Technology MARA (UiTM).As part of the development of Knowledge Management Center project, it was drawn from the theories and practices of knowledge management that can be applied in academic institutions.The objective of the project is to integrate and monitor university knowledge asset, which we believe is an important aspect to drive UiTM as the preferred university in the region. The project is intended to leverage the university work force and technology as a platform to nurture and support knowledge management activities.